Defining Speech Subtypes in De Novo Parkinson Disease: Response to Long-term Levodopa Therapy. (23rd November 2021) - Rusz, Jan; Tykalova, Tereza; Novotny, Michal; Zogala, David; Sonka, Karel; Ruzicka, Evzen; Dusek, Petr
Abstract : Background and Objectives: Patterns of speech disorder in Parkinson disease (PD), which are highly variable across individual patients, have not been systematically studied. Our aim was to identify speech subtypes in treatment-naive patients with PD and to examine their response to long-term dopaminergic therapy. Methods: We recorded speech data from a total of 111 participants with de novo PD; 83 of the participants completed the 12-month follow-up (69 patients with PD on stable dopaminergic medication and 14 untreated controls with PD). Unsupervised k-means cluster analysis was performed on 8 distinctive parameters of hypokinetic dysarthria examined with quantitative acoustic analysis. Results: Three distinct speech subtypes with similar prevalence, symptom duration, and motor severity were detected: prosodic, phonatory-prosodic, and articulatory-prosodic. Besides monopitch and monoloudness, which were common in each subtype, speech impairment was more severe in the phonatory-prosodic subtype with predominant dysphonia and the articulatory-prosodic subtype with predominant imprecise consonant articulation than in the prosodic subtype. Clinically, the prosodic subtype was characterized by a prevalence of women and younger age, while articulatory-prosodic subtype was characterized by the prevalence of men, older age, greater severity of axial gait symptoms, and poorer cognitive performance. The phonatory-prosodic subtype clinically represented intermediate status in age with mostly men and preserved cognitive performance. While speech of untreated controls with PD deteriorated over 1 year ( p = 0.02), long-term dopaminergic medication maintained stable speech impairment severity in the prosodic and articulatory-prosodic subtypes and improved speech performance in patients with the phonatory-prosodic subtype ( p = 0.002). Discussion: Distinct speech phenotypes in de novo PD reflect divergent underlying mechanisms and allow prediction of response of speech impairment to levodopa therapy. Classification of Evidence: This study provides Class II evidence that, in patients with newly diagnosed PD with speech impairment, speech phenotype is associated with levodopa responsiveness.